Perancangan Buku “Jejak Kaki Semar” (The Book Design of “Jejak Kaki Semar”) - Gilang Purnama; Mohammad Isa Pramana Koesoemadinata (Wayang Nusantara: Journal of Puppetry, 2020)
AbstractThe Book Design of “Jejak Kaki Semar”.This paper aimed to discuss the design of a book (book design) as a medium for introducing puppet to the younger generation. This book is entitled Jejak Kaki Semar. This book tells about Semar and its philosophical meaning. It was designed as a medium of information, education, and entertainment. In order to attract the younger generation, this book is given an attractive illustration and sold at a low price.AbstrakTulisan ini membahas tentang perancangan sebuah buku sebagai media memperkenalkan wayang kepada generasi muda. Jadi tulisan ini membahas tentang desain buku dan makna filosofi tokoh Semar. Buku ini diberi judul Jejak Kaki Semar. Buku tentang tokoh Semar dan makna filosofinya ini dirancang sebagai satu media informasi, edukasi dan hiburan. Untuk menarik minat generasi muda, buku ini diberi ilustrasi yang menarik dan dijual dengan harga murah.